OFFLINE OVER THE AIR (OTA) UPDATE PROTOCOL FOR IOT DEVICES USING ESP-NOW FOR AGRICULTURE APPLICATION - Dr S.V.R Manimala; Manipaty Renuka (Utilitas Mathematica, 2025)
Using the ESP-NOW communication protocol, this project presents a unique method for simulating Over-the-Air (OTA) updates in a distributed sensor network based on ESP32 microcontrollers. The suggested ESP-NOW-based system functions independently of internet connectivity and access points, in contrast to conventional Wi-Fi OTA update systems that rely significantly on these elements. This makes it a low-power, effective, and scalable solution that is perfect for agricultural IoT installations. Five ESP32 nodes make up the system architecture, and each one is interfaced with sensors to gather environmental data pertinent to agricultural applications. One of these nodes has an OLED display that allows it to see live sensor data and update status in real time. Versioned messages that dynamically alter data logic are used to imitate firmware changes. A sturdy multi-hop ESP-NOW mesh is used to transmit these signals throughout the network, guaranteeing the timely and dependable distribution of updates throughout the dispersed sensor array. When compared to traditional Wi-Fi OTA techniques, this strategy dramatically improves performance parameters including update speed, energy economy, and communication range. In difficult agricultural settings, the system gains increased flexibility and dependability by doing away with dependence on external network infrastructure. The outcomes confirm that ESP-NOW is a viable and expandable OTA solution designed for smart agriculture IoT systems.